TIME RESERVES DURING THE ORGANISATION OF FREIGHT TRAIN MOVEMENT ON SCHEDULE - Kozachenko, D. M.; Berezovyi, M. I.; Balanov, V. O.; Zhuravel, V. V. (Science and Transport Progress, 2015)
Purpose. The article is devoted to the development of estimation methods of time reserves that should be formed at the train schedule and the schedule for the turnover of freight trains, required to ensure the sustained interaction of technological processes of industrial enterprises and railways for the transportation of freight on schedule. Methodology. The paper considers the issues of bulk conveyance organization between industrial enterprises on schedule. In order to ensure the arrival of trains at the destination station to the specified time, the schedules of rolling stocks turnover must have some time reserves. These reserves, in their turn, should be sufficient for correction action of destabilizing factors. The methods of mathematical statistics were used to study the schedule performance quality of separate trains. Currently the movement of the main part of freight trains is performed on preparedness and occupation processes of separate schedule train paths by some depots are not fixed. Therefore, the analyses of the schedule performance of freight trains do not allow receiving the material for research. And, due to the lack of statistical material on the punctuality of the schedule for the movement of freight trains, research of the passenger trains movement with subsequent dissemination of results on freight movement were carried out by the authors. Findings. The research proved that the trains arrival at the destination station according to the schedule should be ensured by permissible rating of delay as well as increase the operating time of trains and running intervals. The values of the additional time reserves that should be included in the schedule of trains, and the schedule for the turnover of freight trains to provide conditional interaction of railroads and industrial enterprises in Ukraine were proposed. Originality. On the basis of the research development graph methods of trains turnover, providing transportation of goods on schedule were improved. Practical value. The obtained results can be used for the technical-and-economic calculations of transition effectiveness of industrial enterprises for maintenance on schedule as well as in the development of schedule on the initial stages of testing technology.